HUBUNGAN PENDIDIKAN DAN PENGETAHUAN TENTANG GIZI PADA PASIEN GAGAL GINJAL KRONIK TERHADAP ASUPAN ENERGI DAN PROTEIN YANG MENJALANI HEMODIALISIS DI RS IMANUEL BANDAR LAMPUNG - Saleh, Asep Jalaludin; Jayadi, Ajib; Handayani, Sukanti (Jurnal Ilmu Gizi Indonesia (JIGZI), 2023)
Abstract Constant Kidney Disappointment (CKD) is a condition that causes irreversible and irreversible decline in kidney function and the body ignores digestion and fluid and electrolyte balance. The danger factor for persistent kidney failure is diabetes mellitus due to heredity and diet, while another dangerous factor that can cause it is hypertension. If it continues continuously, it can cause kidney work to be hampered. The purpose of this study was to break the relationship between education and knowledge about nutrition of patients with chronic kidney failure on energy and protein intake undergoing hemodialysis at IMANUEL Hospital Bandar Lampung in 2021. The research method used research analytic observational approach with cross sectional study. The data was processed by Chi-square test and fishers exact test with a total of 60 samples. It shows that there is a relationship between education, knowledge of nutrition and energy and protein intake with P value < 0.05. Keywords: education, knowledge, energy_intake, protein_intake.